2014
DOI: 10.1038/srep03659
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced magnetic resonance angiography in brain death

Abstract: Confirmatory tests for the diagnosis of brain death in addition to clinical findings may shorten observation time required in some countries and may add certainty to the diagnosis under specific circumstances. The practicability of Gadolinium-enhanced magnetic resonance angiography to confirm cerebral circulatory arrest was assessed after the diagnosis of brain death in 15 patients using a 1.5 Tesla MRI scanner. In all 15 patients extracranial blood flow distal to the external carotid arteries was undisturbed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…As the regular blood supply to the brain is interrupted, brain cells start dying while at the same time blood swelling elevates the intracranial pressure which compresses the adjacent tissues 1 . Since the ICH (traumatic and non-traumatic) can lead to brain deformation and a huge number of death (mortality rate of 30–50%) and disability (74% survivors) worldwide 2 3 4 , it is a crucial public health issue. On-the-spot accurate detection by means of head imaging is the governing factor of the timely medication to ensure complete recovery of the injured patient 4 5 .…”
mentioning
confidence: 99%
“…As the regular blood supply to the brain is interrupted, brain cells start dying while at the same time blood swelling elevates the intracranial pressure which compresses the adjacent tissues 1 . Since the ICH (traumatic and non-traumatic) can lead to brain deformation and a huge number of death (mortality rate of 30–50%) and disability (74% survivors) worldwide 2 3 4 , it is a crucial public health issue. On-the-spot accurate detection by means of head imaging is the governing factor of the timely medication to ensure complete recovery of the injured patient 4 5 .…”
mentioning
confidence: 99%
“…However, these parameters would place the tests used here alongside other currently investigated methods for brain death confirmation, i.e., computed tomography angiography (sensitivity, 63–87.5% 37 , 39 , 49 ; or diffusion-weighted magnetic resonance imaging (sensitivity 90%) 50 . Other methods that have higher sensitivity and specificity have limited accessibility (Xenon CT) 1 , are difficult to perform (magnetic resonance angiography) 51 , 52 or are operator-dependent (transcranial Doppler; sensitivity 88%, specificity 98%) 53 . We have shown that optical methods based on TR-NIRS are feasible during an ICU stay, available at the bedside, and have promising preliminary results.…”
Section: Discussionmentioning
confidence: 99%
“…veröffentlicht. 2014 publizierten Luchtmann et al[24] eine Studie mit Gd-unterstützter MRA. Probleme hinsichtlich des Einsatzes der MRA zur Feststellung des zerebralen Zirkulationsstilstandes ergeben sich je nach Hersteller aufgrund der sehr unterschiedlichen Sequenzparameter.…”
unclassified